Mapping the methodologies of the craft sciences in Finland, Sweden and Norway. Issue 2 (1st September 2020) - Kokko, Sirpa; Almevik, Gunnar; Bentz Høgseth, Harald C.; Seitamaa-Hakkarainen, Pirita
The craft sciences have emerged as a field of academic research in Finland, Sweden and Norway since the early 1990s. In Finland, craft research has examined various aspects of crafts using a multidisciplinary approach, adapting a range of methods from other academic disciplines according to the research topic. Another source has been the schools of domestic sciences in which craft research has been a recognized field. In Sweden and Norway, craft research has developed strongly in architectural conservation and cultural heritage with a focus on traditional craftsmanship and the performative elements of intangible cultural heritage. This article offers an overview of the developments and progress of the field of craft sciences in these countries, including its methodological approaches, with a focus on Ph.D. theses. Through mapping recurrent methodological approaches, the following categories were derived: craft reconstruction, craft interpretations, craft elicitation, craft amplification and craft socialization. The aim of the classification, and the model derived from it, is to help researchers and students understand better how different types of knowledge relate to different research methods and apply them within their own research. The purpose of the research is to create a common infrastructure for research and education in order to connect and strengthen the dispersed academic communities of craft research and to establish craft science as a formally recognized discipline within the academic system.